2018
DOI: 10.3389/fnagi.2018.00052
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal Connections of Primary Sensory Cortices Largely Vanish During Normal Aging

Abstract: During aging, human response times (RTs) to unisensory and crossmodal stimuli decrease. However, the elderly benefit more from crossmodal stimulus representations than younger people. The underlying short-latency multisensory integration process is mediated by direct crossmodal connections at the level of primary sensory cortices. We investigate the age-related changes of these connections using a rodent model (Mongolian gerbil), retrograde tracer injections into the primary auditory (A1), somatosensory (S1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 97 publications
(157 reference statements)
2
6
0
Order By: Relevance
“…Hence, our results clearly speak towards a reduced peripheral acuity in the OA and confirm a previous study, which found no difference in the a priori binding tendency with age in healthy individuals (Jones et al, 2019). Hence, despite changes in neurophysiological markers of sensory encoding and cognition as well as changes in general brain structure with age (Henry et al, 2017;Henschke et al, 2018;McNair et al, 2019) the converging evidence suggests that multisensory perception in healthy aging is mostly affected by changes in peripheral sensory processes.…”
Section: Changes In Within-trial Multisensory Integration With Agesupporting
confidence: 89%
See 1 more Smart Citation
“…Hence, our results clearly speak towards a reduced peripheral acuity in the OA and confirm a previous study, which found no difference in the a priori binding tendency with age in healthy individuals (Jones et al, 2019). Hence, despite changes in neurophysiological markers of sensory encoding and cognition as well as changes in general brain structure with age (Henry et al, 2017;Henschke et al, 2018;McNair et al, 2019) the converging evidence suggests that multisensory perception in healthy aging is mostly affected by changes in peripheral sensory processes.…”
Section: Changes In Within-trial Multisensory Integration With Agesupporting
confidence: 89%
“…One of the commonly known features of healthy aging is losing the 'sharpness' -such as the precision of sensory perception (Dobreva et al, 2011;Lindenberger & Baltes, 1994;Otte et al, 2013;Salthouse, 1996), that of memory (Salthouse, 2010(Salthouse, , 2019, or the swiftness of responses (Falkenstein et al, 2006;Jones et al, 2019). Such changes in perception are accompanied by alterations in brain structure or brain activity with age (Henry et al, 2017;Henschke et al, 2018;McNair et al, 2019), suggesting that aging may affect both early sensory and higher level cognitive processes (Diaconescu et al, 2013;Dully et al, 2018;Henry et al, 2017;McNair et al, 2019;Nunez, 2015;Zanto & Gazzaley, 2014). Unravelling the mechanisms by which perception changes with age becomes particularly challenging when behavior relies on the combination of multiple sensory or behavioral attributes, such as during multisensory integration or the adaptive trial-by-trial recalibration of perception based on previous multisensory experience (also known as after-effects).…”
Section: Introductionmentioning
confidence: 99%
“…For identification of layer III pyramidal neurons also other cytoarchitectural features were considered such as the absence of pyramidal cell somata in layer IV and the smaller size of pyramidal neurons in layer II compared to layer III (for review, see Nieuwenhuys, 1994; Bannister, 2005; Winer, 2011; Budinger and Kanold, 2018). The different ages of the animals used in the current (P28) and previous studies (P120; Budinger et al, 2013; Mylius et al, 2013; Radtke-Schuller et al, 2016) had not to be considered because the brain size and in particular the cortical thickness does not significantly change from P28 towards P120 animals (Wilkinson, 1986; Henschke et al, 2018a,b).…”
Section: Methodsmentioning
confidence: 92%
“…The Mongolian gerbil is also a favorable species for research on development and aging (Vincent et al, 1980; Cheal, 1986; Henschke et al, 2018a,b). At birth, Mongolian gerbils are deaf and blind (Souter et al, 1997) but show first sensorimotor reflexes (Cabana et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…CC-BY 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted June 14, 2021. ; https://doi.org/10.1101/2021.06.14.448057 doi: bioRxiv preprint As well as targeting multiple cortical layers, TC connections that are developing during this early postnatal period have been found to project to multiple cortical regions, some of which are developmentally transient connections and some which persist throughout adulthood (Henschke et al, 2015(Henschke et al, , 2017(Henschke et al, , 2018. These cross-modal connections may be responsible for coordinated cortical activity such as between S1 and M1 found in our study.…”
Section: Development Of Spontaneous Activitymentioning
confidence: 99%